Civic engagement penyandang disabilitas dalam memperjuangkan hak atas pekerjaan (studi pada induk disabilitas Purworejo) - Mulia, Ibnata Bikry; Yuliandari, Erna; Hartanto, Rima Vien Permata (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Work is self-actualization by channeling and developing abilities to be more productive to achieve a prosperous life. Work is one of the rights that every person, including people with disabilities, is born with, and must be fulfilled and respected. However, in its implementation, there is a lack of attention from the authorities related to employment issues and legal guarantees. This research analyzes the civic engagement of people with disabilities through Induk Disabilitas Purworejo, in which the majority of members are people with physical disabilities fighting for their right to work. This research also analyzes the supporting and inhibiting factors for the success of civic engagement. The research method is qualitative with purposive sampling. Research data were gathered through observation, interviews, and document studies. The result of the discussion is that the civic engagement of people with disabilities through Induk Disabilitas Purworejo in fighting for the right to work is actualized through activity programmes such as advocacy, working with local agencies and opening small trainings at regular meetings in accordance with the components and indicators of civic engagement. In addition, there are supporting factors that are analyzed such as motivation and a sense of responsibility and skills from people with disabilities supported by the role of family, Induk Disabilitas Purworejo assistants, wheelchair aids, and civic cohesion. There are inhibiting factors that affect civic engagement, namely the lack of attention from the Regent regarding the guarantee of legal rights for people with disabilities and lack of accessibility during the implementation of activity programmes.